Methods of teaching Turkmen students the morphological indicators of the Russian language - Іванова, Т. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The comparison of some morphological characteristics of Russian and Turkmen languages has been given in the article. The above languages belong to different groups: Russian refers to the group of inflectional languages, and Turkmen is included into an agglutinative group. Unlike the Russian language, all forms of changes in the stem are divided into two main groups in the Turkmen language: word-formative and form-building. In Russian and Turkmen languages stems are divided into derivative and non-productive. In both languages the non-productive stem consists of one root, and the derivative stem has more complicated structure. Prefixes and suffixes of the Russian language are a part of the stem, and Turkmen word stems have actually from one to three and more affixes which play another role as opposed to the Russian one. Having acquainted students at the initial stage of the target language training with the peculiarities of the word structure and some features of the word formation in the Russian language, it would be appropriate to show external formal indicators for defining different words’ belonging to a certain part of speech. The parts of speech in both languages are divided into two categories: notional an functional. When facing with each part of speech, it is important to show specific distinctive peculiarities of Russian (in comparison with the Turkmen language). Unlike the Russian language, gender as a grammatical category is absent in Turkmen. Nouns in both languages alter their form to reflect the case and have a category of number therefore these grammar parts don’t cause difficulties training the target language. No difficulty arose that Russian nouns in singular have three types of the declension, and the only one in the Turkmen language. The presentation of distinctive peculiarities of Russian and Turkmen morphology in teaching the target language takes a central place as the system of the second language is imprinted much better in the students’ consciousness if it is represented by means of native and target languages comparison. While comparing Russian and Turkmen grammar units’ meaning, it is easier for the students to acquire grammar material and use it in the speech in a correct way.